Islanding Detection and Enhancement of Microgrid Performance - Pouryekta A.; Ramachandaramurthy V.K.; Mithulananthan N.; Arulampalam A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Controllers; Distributed power generation; Electric equipment protection; Electric load flow; Power control; Renewable energy resources; System stability; Voltage control; Adaptive control strategy; Autonomous operations; Dispersed generation units; Islanding detection; Islanding detection methods; Multiple distributed generations; Renewable energy source; Scheduled maintenance plans; Adaptive control systems